CASH FLOW ANALYSIS OF NON-MANUFACTURING ENTERPRISES - Kulchev, Krasimir (E-Journal VFU, 2024)
When evaluating the financial condition of enterprises, the ratios involving cash flows are of paramount importance. These indicators are applied in financial analysis, including in discriminating financially stable business organizations from enterprises at an increased risk of bankruptcy. The present paper aims to calculate the average values of some ratios involving cash flows, and the research has been done based on information from the financial statements of non-manufacturing enterprises.
Keywords: cash flows; financial ratios; financial condition; financial analysis